The profile of soccer injuries and their management amongst the premier soccer teams in Lesotho - Mokhochane, Rethabile Dineo (Sefako Makgatho Medical University, 2013)
Introduction: Soccer predisposes its players to a number of injuries which could adversely affect the player’s career if relevant management is not instituted. The aim of the study was to develop a profile of soccer injuries amongst the premier soccer teams in Lesotho and determine a need for physiotherapy intervention. Methodology: A cross sectional descriptive survey was used. Simple random selection was used to select a total of 201 soccer players from 12 premier teams participated in the study. Inferential statistics were performed using ANOVA, ANCOVA and Pearson’s correlation coefficient tests to determine the relationship of the players’ injuries, contributing factors and their management. Questionnaire’s validity and reliability were established by physiotherapist working with athletes. Results: The lower limb is the commonly affected body part with the ankle sustaining most injuries (36.4%). Common types of injuries were muscle strains (32.4%) and ligament sprains (23.0%). Mechanisms of injury during competitive games and training sessions include being tackled (25.2%); landing, tackling and overuse. Injuries sustained are treated sometimes by medical personnel (43.7%), traditional or home remedies (41.7%) and physiotherapist (29.6%). Ankle injuries are associated with self- treat (p= 0.020). There is a strong significant relationship between the mode of treatment (not physiotherapy) and common injuries that occurred amongst the players (p<0.05). The common mechanism of injury is also association with the common injuries that occurred (p<0.05). Conclusion and implications: Injuries occurring amongst soccer players in the Lesotho Premier Soccer League are sprains and strains and no consistent management is available for the injured players. The type and severity of common injuries indicate their impact on the soccer sporting activity. The injured player ceases activity immediately after injury. Soccer fraternity need to pay attention to provision of physiotherapy services and players have to be educated regarding appropriate injury prevention and management strategies.
Thesis (M.Sc.( Sports Physiotherapy and Rehabilitation)) --Sefako Makgatho Medical University, 2013.
Keywords: Profile; Management; Premier Soccer teams; Lesotho; Soccer injuries; 617.102706; Sports physical therapy; Therapeutics, Physiological; Physiotherapy